UMP and ECER adopts blue ocean strategy to help improve the living standards of people in rural areas - Zainal, Bahari (Penerbit UMP, 2014)
East Coast Economic Region Development Council (ECERDC) conducted a human resource development programme aimed at providing job opportunities to people in the rural area. The focus was on the hard core poor, women and youths so they would have better living standards. It also gave the opportunity for Universiti Malaysia Pahang (UMP) to play a role and contribute to the local community.